Polyphenolic compounds as novel reno-modulatory agents in the management of diabetic nephropathy in Wistar rats - Chhetri, Royan; Kumar N, Prem (The Scientific Temper, 2024)
Diabetic nephropathy (DN), a prevalent diabetes-related complication that leads to end-stage kidney failure due to functional changes in the renal system. Contemporary antidiabetic interventions effectively fail to prevent or slow down the course of diabetic kidney damage. The current study investigates the impact of Coccinia indica ethanolic leaf extract (CILE) both individually and combined with hesperidin, a bioflavonoid, to mitigate the advancing renal damage induced by non-insulin-dependent diabetes mellitus in a rodent model. DN was triggered in experimental rats by administering a high-fat diet and, thereafter, by a single injection of streptozotocin (35 mg/kg, intraperitoneally). The experimental groups received CILE, hesperidin (high and low dose), C. indica in conjugation with low-dose hesperidin and metformin alone during the treatment period. The study evaluated several parameters, including serum glucose, antioxidant levels, blood urea nitrogen, urine protein levels, creatinine, and inflammatory mediators (interleukin-6 and tumor necrosis factor-alpha). These parameters were also studied in negative control animals to understand and compare the therapeutic potential of polyphenolic compounds. The histomorphological study coincides with the elevated biomarkers observed in the non-intervention groups. The treatment with different predetermined therapies normalized all biomarkers toward normal levels, including histopathological changes. Therefore, administration of hesperidin and CILE showed significant benefits in delaying the progression of kidney damage and presents promising potential therapy for managing DN.